Euler tours in hypergraphs - Glock, Stefan; Joos, Felix; Kühn, Daniela; Osthus, Deryk (Combinatorica, 2020)
We show that a quasirandom k-uniform hypergraph G has a tight Euler tour subject to the necessary condition that k divides all vertex degrees. The case when G is complete confirms a conjecture of Chung, Diaconis and Graham from 1989 on the existence of universal cycles for the k-subsets of an n-set.
Gesehen am 27.07.2022